AVR2 Targets BSL Family Members, Which Act as Susceptibility Factors to Suppress Host Immunity. Issue 1 (19th February 2019) - Turnbull, Dionne; Wang, Haixia; Breen, Susan; Malec, Marek; Naqvi, Shaista; Yang, Lina; Welsh, Lydia; Hemsley, Piers; Zhendong, Tian; Brunner, Frederic; Gilroy, Eleanor M.; Birch, Paul R.J.
Abstract : Late blight pathogen Phytophthora infestans uses effector Avr2 to target BSL phosphatases to suppress plant immunity. Abstract: To be successful plant pathogens, microbes use "effector proteins" to manipulate host functions to their benefit. Identifying host targets of effector proteins and characterizing their role in the infection process allow us to better understand plant–pathogen interactions and the plant immune system. Yeast two-hybrid analysis and coimmunoprecipitation were used to demonstrate that the Phytophthora infestans effector AVIRULENCE 2 (PiAVR2) interacts with all three BRI1-SUPPRESSOR1-like (BSL) family members from potato ( Solanum tuberosum ). Transient expression of BSL1, BSL2, and BSL3 enhanced P. infestans leaf infection. BSL1 and BSL3 suppressed INFESTIN 1 elicitin-triggered cell death, showing that they negatively regulate immunity. Virus-induced gene silencing studies revealed that BSL2 and BSL3 are required for BSL1 stability and show that basal levels of immunity are increased in BSL -silenced plants. Immune suppression by BSL family members is dependent on the brassinosteroid-responsive host transcription factor CIB1/HBI1-like 1. The P. infestans effector PiAVR2 targets all three BSL family members in the crop plant S. tuberosum . These phosphatases, known for their role in growth-promoting brassinosteroid signaling, all support P. infestans virulence and thus can be regarded as susceptibility factors in late blight infection.